It Takes Two to Tango: How Customer Orientation and Innovation Behavior Synergize to Drive MSMEs' Performance - Darmawan, Baziedy Aditya; Khoiri, Ahmad Rizal (Profesional Muda Cendekia Publishing, 2024)
Research Aims: Despite being a key contributor to the national economy, MSMEs face significant challenges in enhancing their performance. Although previous studies have identified customer orientation as a critical factor in improving organizational performance, there is a lack of clarity regarding the role of innovation behavior in this relationship. Therefore, this study aims to investigate the mediating role of innovation behavior in the relationship between customer orientation and MSMEs’ performance. Design/methodology/approach: The study reviews previous literature to formulate hypotheses and develop a research model. Data were collected from 76 MSMEs across various industries in Yogyakarta and Sleman. The collected data were analyzed using the PLS-SEM approach to evaluate the measurement model and test the formulated hypotheses. Research Findings: The findings reveal that innovation behavior fully mediates the relationship between customer orientation and MSMEs’ performance. Additionally, customer orientation plays a crucial role in fostering innovation behavior within MSMEs. Theoretical Contribution/Originality: This study confirms that innovation behavior is an essential factor that needs to be synergized with customer orientation to ensure its effectiveness in driving improved MSMEs’ performance.